Non-aqueous electrolyte power storage element, device, method for using non-aqueous electrolyte power storage element, and method for manufacturing non

The positive electrode potential of the discharge termination voltage is set to 3.5V by using a positive electrode active material having a ratio of 5 or less to an average particle size to an average primary particle size and a compound containing sulfur element of 0.5% by mass in the nonaqueous electrolyte power storage element. (vs.Li/Li+) below solves the problem of reduced capacity after charging and discharging, and achieves the effect of high capacity maintenance and low DC resistance.

CN119487660APending Publication Date: 2025-02-18GS YUASA INT LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380051728.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-06
Filing Date
2023-07-05
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When the discharge termination voltage is set to be low and the positive electrode potential reaches a low potential is repeated, the discharge capacity of the nonaqueous electrolyte storage element is easily reduced, and when the compound containing sulfur element is contained, the capacity maintenance rate is maintained Instead, it is reduced.

Method used

The positive electrode containing a positive electrode active material having a ratio of 5 or less to an average particle size, and a compound containing sulfur element of 0.5 mass% or more is contained in the nonaqueous electrolyte, and the positive electrode potential of the discharge termination voltage is set to 3.5. V(vs.Li/Li+) or below.

Benefits of technology

The capacity maintenance rate after the charge and discharge cycle is improved, the initial DC resistance is reduced, the service life of the nonaqueous electrolyte power storage components is extended, and the replacement frequency is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487660A_ABST
    Figure CN119487660A_ABST
Patent Text Reader

Abstract

A non-aqueous electrolyte electricity storage element according to one aspect of the present invention has a positive electrode potential of 3.5 V (vs. Li / Li +) or less at a discharge end voltage during normal use, and is provided with: a positive electrode containing a positive electrode active material having a ratio of an average particle diameter to an average primary particle diameter of 5 or less; and a non-aqueous electrolyte containing a compound containing elemental sulfur.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a nonaqueous electrolyte energy storage element, a device, a method for using the nonaqueous electrolyte energy storage element, and a method for manufacturing the nonaqueous electrolyte energy storage element. Background Art

[0002] Non-aqueous electrolyte secondary batteries represented by lithium-ion secondary batteries are often used in electronic devices such as personal computers, communication terminals, and automobiles due to their high energy density. Non-aqueous electrolyte secondary batteries are generally composed of a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte between the electrodes, and are charged and discharged by transferring charge ions between the two electrodes. As non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium-ion capacitors and double-layer capacitors have also been widely popularized.

[0003] In order to improve the performance of non-aqueous electrolyte storage devices, studies have been conducted on incorporating various additives into non-aqueous electrolytes. Patent Document 1 describes a non-aqueous secondary battery having a non-aqueous electrolyte containing an additive such as a cyclic sulfate ester.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2003-308875 Summary of the invention

[0007] By setting the discharge end voltage of the non-aqueous electrolyte storage element to be relatively low, the amount of electricity extracted from the non-aqueous electrolyte storage element, that is, the discharge capacity, can be increased. However, in the case where the discharge end voltage is set relatively low and the charge and discharge are repeated with the positive electrode potential reaching a low potential, a decrease in discharge capacity due to repeated charge and discharge is likely to occur. As a means of suppressing the decrease in discharge capacity due to repeated charge and discharge, it is possible to consider including additives such as compounds containing sulfur in the non-aqueous electrolyte. However, in the case where the discharge end voltage is set relatively low and the positive electrode potential is repeatedly reached A low potential (for example, 3.5V (vs.Li / Li + ) or less), when the non-aqueous electrolyte contains a compound containing elemental sulfur, the effect of suppressing the decrease in capacity retention rate after charge and discharge cycles is not produced, but the capacity retention rate is sometimes further reduced.

[0008] The present invention aims to provide a discharge termination voltage of the positive electrode potential of 3.5V (vs. Li / Li +) or less and having a high capacity retention rate after charge and discharge cycles, a device having such a non-aqueous electrolyte storage element, a method for using such a non-aqueous electrolyte storage element, and a method for manufacturing such a non-aqueous electrolyte storage element.

[0009] The positive electrode potential of the discharge end voltage of the nonaqueous electrolyte storage element of one aspect of the present invention during normal use is 3.5 V (vs. Li / Li + ) or less, and comprises: a positive electrode containing a positive electrode active material having a ratio of an average particle size to an average primary particle size of 5 or less, and a non-aqueous electrolyte containing a compound containing sulfur element.

[0010] A device according to another aspect of the present invention includes the nonaqueous electrolyte storage element according to one aspect of the present invention.

[0011] A method for using a non-aqueous electrolyte storage element according to another aspect of the present invention comprises: discharging a non-aqueous electrolyte storage element having a positive electrode containing a positive electrode active material having a ratio of an average particle size to an average primary particle size of 5 or less and a non-aqueous electrolyte containing a compound containing elemental sulfur until the positive electrode potential reaches 3.5 V (vs. Li / Li + )the following.

[0012] Another aspect of the present invention is a method for producing a non-aqueous electrolyte storage element having a positive electrode potential of 3.5 V (vs. Li / Li) at a discharge end voltage during normal use. + ) below, comprising: preparing a positive electrode containing a positive electrode active material having a ratio of an average particle size to an average primary particle size of less than 5; and preparing a non-aqueous electrolyte containing a compound containing sulfur element; the content of the compound containing sulfur element in the above-mentioned non-aqueous electrolyte is greater than 0.5% by mass.

[0013] According to any aspect of the present invention, a positive electrode potential of a discharge end voltage of 3.5 V (vs. Li / Li) can be provided. + ) or less and having a high capacity retention rate after charge and discharge cycles, a device having such a non-aqueous electrolyte storage element, a method for using such a non-aqueous electrolyte storage element, and a method for manufacturing such a non-aqueous electrolyte storage element. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a perspective view showing one embodiment of a non-aqueous electrolyte electricity storage element.

[0015] Figure 2 This is a schematic diagram showing one embodiment of an electricity storage device constituted by assembling a plurality of nonaqueous electrolyte electricity storage elements. DETAILED DESCRIPTION

[0016] First, the outlines of the nonaqueous electrolyte electricity storage element, device, method of using the nonaqueous electrolyte electricity storage element, and method of manufacturing the nonaqueous electrolyte electricity storage element disclosed in this specification are described.

[0017] [1] The positive electrode potential of the nonaqueous electrolyte storage element according to one aspect of the present invention at the discharge end voltage during normal use is 3.5 V (vs. Li / Li + ) or less, comprising: a positive electrode containing a positive electrode active material having a ratio of an average particle size to an average primary particle size of 5 or less, and a non-aqueous electrolyte containing a compound containing sulfur element.

[0018] The non-aqueous electrolyte storage element described in [1] above has a positive electrode potential of 3.5 V (vs. Li / Li) at a discharge end voltage during normal use. + ) or less, the capacity retention rate after charge and discharge cycles is high. The reason is not clear yet, but it can be inferred as follows. The compound containing sulfur contained in the non-aqueous electrolyte decomposes to form a film of active material covering the positive and negative electrodes. It is believed that the film formed on the surface of the active material can play an effect of suppressing the decrease in discharge capacity. However, it is believed that when the positive electrode potential reaches 3.5V (vs.Li / Li + ) or less, the positive electrode active material is prone to rupture, and when the non-aqueous electrolyte contains a compound containing the elemental sulfur, the rupture of the positive electrode active material is promoted by the influence of the acid, which is a decomposition byproduct of the compound containing the elemental sulfur. Such rupture of the positive electrode active material causes a decrease in discharge capacity. On the other hand, the positive electrode active material having a ratio of average particle size to average primary particle size of 5 or less is a granular material formed by a small amount of primary particles, and is therefore not prone to rupture. Therefore, in a non-aqueous electrolyte storage element using such a positive electrode active material, even if the non-aqueous electrolyte contains a compound containing the elemental sulfur and the positive electrode potential reaches 3.5V (vs. Li / Li + ) or less, the positive electrode active material is not easily broken, and the protective effect of the active material surface brought by the compound containing sulfur element is fully exerted. For this reason, the non-aqueous electrolyte storage element described in [1] is a non-aqueous electrolyte storage element with a positive electrode potential of 3.5V (vs. Li / Li) at the discharge end voltage during normal use. + ) or less, it is presumed that the non-aqueous electrolyte storage element has a high capacity retention rate after charge and discharge cycles.

[0019] “In normal use” means that the nonaqueous electrolyte storage element is used under the charge and discharge conditions recommended or specified for the nonaqueous electrolyte storage element. The discharge conditions are determined, for example, by the settings of the device in which the nonaqueous electrolyte storage element is used.

[0020] The "average primary particle size" of the positive electrode active material refers to the average value of the primary particle sizes of any 50 primary particles constituting the positive electrode active material observed in a scanning electron microscope (SEM). Primary particles refer to particles whose grain boundaries cannot be observed in appearance during observation with the above-mentioned SEM. The primary particle size of the primary particle is calculated as follows. The shortest diameter passing through the center of the minimum circumscribed circle of the primary particle is set as the short diameter, and the diameter passing through the above-mentioned center and orthogonal to the short diameter is set as the long diameter. The average value of the long diameter and the short diameter is set as the primary particle size. When there are more than two shortest diameters, the longest orthogonal diameter is set as the short diameter.

[0021] The "average particle size" of the positive electrode active material refers to the value of 50% (D50: median diameter) of the volume-based cumulative distribution calculated according to JIS-Z-8819-2 (2001) based on the particle size distribution measured by the laser diffraction and scattering method of the diluted solution obtained by diluting the positive electrode active material with a solvent in accordance with JIS-Z-8815 (2013). It should be noted that it was confirmed that the average particle size based on the above measurement was roughly consistent with the average particle size of each secondary particle extracted from the SEM image of the particle avoiding extremely large particles and extremely small particles, that is, the average secondary particle size. The particle size of each secondary particle measured based on the measurement of the SEM image is calculated as follows. The SEM image is obtained based on the above-mentioned situation of calculating the "average primary particle size". The shortest diameter passing through the center of the minimum circumscribed circle of each secondary particle is set as the short diameter, and the diameter passing through the above center and orthogonal to the short diameter is set as the long diameter. The average value of the long diameter and the short diameter is set as the particle size of each secondary particle. When there are two or more shortest paths, the longest orthogonal path is taken as the shortest path.

[0022] The positive electrode active material for which the average primary particle size and the average particle size are measured is the positive electrode active material before charge and discharge or when it reaches a fully discharged state by the following method. First, the non-aqueous electrolyte storage element is charged at a constant current of 0.05C until the charge termination voltage during normal use is reached, becoming a fully charged state. After resting for 30 minutes, discharge at a constant current of 0.05C to the lower limit voltage during normal use. Disassemble and remove the positive electrode, assemble a half-cell using a metal lithium electrode as the counter electrode, and discharge at a constant current of 10mA per 1g of positive electrode active material until the positive electrode potential reaches 3.0V vs.Li / Li +, adjust the positive electrode to a fully discharged state. Disassemble and remove the positive electrode again. Use dimethyl carbonate to thoroughly clean the non-aqueous electrolyte attached to the removed positive electrode, dry it overnight at room temperature, and then recover the positive electrode active material. The recovered positive electrode active material is provided for measurement. The operation from disassembling the non-aqueous electrolyte storage element to recovering the positive electrode active material is carried out in an argon atmosphere with a dew point below -60°C.

[0023] [2] In the nonaqueous electrolyte storage device described in [1] above, the compound containing elemental sulfur is preferably a sulfate ester.

[0024] The nonaqueous electrolyte energy storage device described in the above [2] has a high capacity retention rate after charge and discharge cycles and can also have a low initial direct current resistance.

[0025] [3] In the nonaqueous electrolyte storage element described in [1] or [2] above, the nonaqueous electrolyte preferably further contains lithium difluorophosphate.

[0026] The nonaqueous electrolyte energy storage device described in the above [3] has a higher capacity retention rate after charge and discharge cycles.

[0027] [4] A device according to another aspect of the present invention comprises the nonaqueous electrolyte storage element according to any one of [1] to [3] above.

[0028] The non-aqueous electrolyte storage element of the device described in [4] above has a positive electrode potential of 3.5 V (vs. Li / Li) at the discharge end voltage during normal use. + ) or less, the capacity retention rate after charge-discharge cycles is high. Therefore, the device described in [4] can be used for a long time, and the replacement frequency of the non-aqueous electrolyte storage element can be reduced.

[0029] [5] A method for using a non-aqueous electrolyte storage element according to another aspect of the present invention comprises: discharging a non-aqueous electrolyte storage element having a positive electrode containing a positive electrode active material having a ratio of an average particle size to an average primary particle size of 5 or less and a non-aqueous electrolyte containing a compound containing elemental sulfur until the positive electrode potential reaches 3.5 V (vs. Li / Li + )the following.

[0030] In the method for using the non-aqueous electrolyte storage device described in [5] above, even if the positive electrode potential of the non-aqueous electrolyte storage device reaches 3.5 V (vs. Li / Li + ), but the capacity retention rate after charge-discharge cycles is high. Therefore, the method for using the non-aqueous electrolyte storage element described in [5] above can use the non-aqueous electrolyte storage element for a long time, and can also reduce the replacement frequency of the non-aqueous electrolyte storage element.

[0031] [6] Another aspect of the present invention is a method for producing a non-aqueous electrolyte storage element having a positive electrode potential of 3.5 V (vs. Li / Li) at a discharge end voltage during normal use. + ) below, comprising: preparing a positive electrode containing a positive electrode active material having a ratio of an average particle size to an average primary particle size of less than 5; and preparing a non-aqueous electrolyte containing a compound containing sulfur element; the content of the compound containing sulfur element in the above-mentioned non-aqueous electrolyte is greater than 0.5% by mass.

[0032] According to the method for producing a non-aqueous electrolyte storage element described in [6], a positive electrode potential of a discharge end voltage in normal use of 3.5 V (vs. Li / Li + ) or less and having a high capacity retention rate after charge and discharge cycles.

[0033] A non-aqueous electrolyte storage element, a storage device, an apparatus, a method for using a non-aqueous electrolyte storage element, a method for manufacturing a non-aqueous electrolyte storage element, and other embodiments of an embodiment of the present invention are described in detail. It should be noted that the names of the components (constituent elements) used in each embodiment are sometimes different from the names of the components (constituent elements) used in the background art.

[0034] <Non-aqueous electrolyte energy storage device>

[0035] A nonaqueous electrolyte storage element (hereinafter also referred to as "storage element") according to one embodiment of the present invention comprises: an electrode body having a positive electrode, a negative electrode and a separator; a nonaqueous electrolyte; and a container for accommodating the electrode body and the nonaqueous electrolyte. The electrode body is generally a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are stacked via a separator, or a wound type in which a positive electrode and a negative electrode are wound in a state where they are stacked via a separator. The nonaqueous electrolyte exists in a state impregnated in the positive electrode, the negative electrode and the separator. As an example of a nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery (hereinafter also referred to as "secondary battery") is described.

[0036] (positive electrode)

[0037] The positive electrode includes a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer.

[0038] The positive electrode substrate has electrical conductivity. Whether it has "electrical conductivity" is determined by measuring the volume resistivity of 10 -2Ω·cm is used as the threshold value for determination. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, or their alloys can be used. Among them, from the viewpoints of potential resistance, high conductivity and cost, aluminum or aluminum alloys are preferred. As the positive electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the viewpoint of cost, foil is preferred. Therefore, as the positive electrode substrate, aluminum foil or aluminum alloy foil is preferred. As aluminum or aluminum alloy, A1085, A3003, A1N30, etc. specified in JIS-H-4000 (2014) or JIS-H-4160 (2006) can be exemplified.

[0039] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By making the average thickness of the positive electrode substrate within the above range, the strength of the positive electrode substrate can be increased, and the energy density per unit volume of the non-aqueous electrolyte storage element can be increased.

[0040] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer reduces the contact resistance between the positive electrode substrate and the positive electrode active material layer by including a conductive agent such as carbon particles. The composition of the intermediate layer is not particularly limited, and for example, includes a binder and a conductive agent.

[0041] The positive electrode active material layer contains a positive electrode active material and may contain any component such as a conductive agent, a binder, a thickener, and a filler as required.

[0042] The positive electrode active material includes particles having a ratio of an average particle size to an average primary particle size of 5 or less (hereinafter also referred to as "single-particle particles"). The ratio of the average particle size to the average primary particle size of the single-particle particles is preferably 4 or less, more preferably 3 or less, and further preferably 2.5 or less. By making the ratio of the average particle size to the average primary particle size below the above upper limit, the advantages of the single-particle particles such as being less prone to breakage can be fully utilized. The lower limit of the ratio of the average particle size to the average primary particle size of the single-particle particles may be 1. It should be noted that since the method for determining the average primary particle size is different from the method for determining the average particle size, the lower limit of the ratio of the average particle size to the average primary particle size may be less than 1, for example, 0.9. The ratio of the average particle size to the average primary particle size of the single-particle particles may be any of the above lower limits to any of the above upper limits.

[0043] The single-particle particles may be particles composed of primary particles (single particles), secondary particles composed of agglomerates of a plurality of primary particles, or mixed particles of single particles and secondary particles, as long as the ratio of the average particle size to the average primary particle size is 5 or less.

[0044] The positive electrode active material constituting the single-particle system particles can be appropriately selected from known positive electrode active materials. As the positive electrode active material for lithium-ion secondary batteries, materials that can absorb and release lithium ions are generally used. Examples of positive electrode active materials include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, sulfur, and the like. Examples of lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni (1-x) ]O2(0≤x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O2 (0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Co (1-x) ]O2(0≤x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2 (0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β) etc. As lithium transition metal composite oxides having a spinel crystal structure, Li x Mn2O4、Li x Ni γ Mn (2-γ) O4, etc. As polyanion compounds, LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. can be cited. As chalcogen compounds, titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. can be cited. The atoms or polyanions in these materials can be partially replaced by atoms or anions composed of other elements. The positive electrode active material can use one of these materials alone, or two or more can be mixed.

[0045] As the positive electrode active material constituting the single-particle system particles, a lithium transition metal composite oxide having an α-NaFeO2 type crystal structure is preferred. In other words, the single-particle system particles are preferably particles of a lithium transition metal composite oxide having an α-NaFeO2 type crystal structure. As such a lithium transition metal composite oxide, it may contain a nickel element, may contain a nickel element and a cobalt element, or may contain a nickel element, a cobalt element, and at least one of a manganese element and an aluminum element. From the viewpoint of electronic conductivity, etc., a lithium transition metal composite oxide containing such an element is usually used in the form of secondary particles formed by agglomeration of multiple primary particles such that the ratio of the average particle size to the average primary particle size exceeds 5, and is prone to rupture with charge and discharge cycles. Therefore, when one embodiment of the present invention is applied to a non-aqueous electrolyte storage element using a lithium transition metal composite oxide containing such an element, the effect of improving the capacity retention rate after charge and discharge cycles is particularly significant.

[0046] The content of nickel element in the lithium transition metal composite oxide is preferably 30 mol % to 100 mol %, more preferably 40 mol % to 90 mol %, and further preferably 50 mol % to 80 mol % based on the metal element other than lithium element.

[0047] The content of cobalt element in the lithium transition metal composite oxide is preferably 5 mol % to 70 mol %, more preferably 10 mol % to 50 mol %, and further preferably 15 mol % to 40 mol % based on the metal element other than lithium element.

[0048] The content of manganese element in the lithium transition metal composite oxide is preferably 5 mol % to 70 mol %, more preferably 10 mol % to 50 mol %, and further preferably 15 mol % to 40 mol % based on the metal element other than lithium element.

[0049] The content of aluminum in the lithium transition metal composite oxide relative to the metal element other than lithium is preferably 0 mol% to 10 mol%, and may be 0.1 mol% to 5 mol%. The content of aluminum in the lithium transition metal composite oxide relative to the metal element other than lithium may be 1 mol% or less, and may be 0 mol%.

[0050] The lithium transition metal composite oxide may further contain other metal elements other than lithium, nickel, cobalt, manganese and aluminum. However, the total content of nickel, cobalt, manganese and aluminum in the lithium transition metal composite oxide relative to the metal elements other than lithium is preferably 80 mol% or more, 90 mol% or more, 95 mol% or more, 99 mol% or more or 100 mol%.

[0051] As the lithium transition metal composite oxide, a compound represented by the following formula (1) can be preferably used.

[0052] Li 1+α Me 1-α O2···(1)

[0053] In formula (1), Me is a metal element other than Li. 0≤α<1.

[0054] α in formula (1) can be 0 to 0.5, 0 to 0.3, 0 to 0.1, or 0. Me can be composed of one or more metal elements. The type of specific metal elements constituting Me (metal elements other than Li) and their content (composition ratio) can adopt the values ​​of each metal element and its preferred content contained in the above-mentioned lithium transition metal composite oxide.

[0055] The composition ratio of the lithium transition metal composite oxide refers to the composition ratio before charge and discharge, or the composition ratio in a fully discharged state by a method of fully discharging the positive electrode active material.

[0056] The average particle size (average primary particle size) of the primary particles constituting the single-particle particles may be, for example, 0.1 μm to 10 μm, 0.3 μm to 5 μm, or 1 μm to 3 μm.

[0057] The average particle size of single-particle particles (positive electrode active materials having a ratio of average particle size to average primary particle size of 5 or less) is preferably, for example, 0.1 μm to 20 μm, more preferably 0.5 μm to 15 μm, further preferably 1 μm to 12 μm, and further preferably 3 μm to 10 μm. By making the average particle size of single-particle particles greater than the above lower limit, the manufacture or handling of single-particle particles becomes easier. By making the average particle size of single-particle particles less than the above upper limit, the electronic conductivity of the positive electrode active material layer is improved.

[0058] Single-particle system particles can be manufactured by a known method, and commercial products can also be used for single-particle system particles. In the manufacturing process of the positive electrode active material, by increasing the sintering temperature or extending the sintering time, the crystals of multiple primary particles are grown and the primary particle size is increased, and single-particle system particles can be obtained. Alternatively, single-particle system particles can be made by crushing secondary particles.

[0059] In order to obtain single-particle particles with a specified particle size (average particle size), a pulverizer, a classifier, etc. can be used. As a pulverization method, for example, a method using a mortar, a ball mill, a sand mill, a vibrating ball mill, a planetary ball mill, a jet mill, a reverse jet mill, a rotating airflow type jet mill or a sieve can be cited. During pulverization, wet pulverization in which organic solvents such as water or hexane coexist can also be used. As a classification method, a sieve, a wind classifier, etc. can be used together with a dry method or a wet method as needed.

[0060] The content of the single-particle system particles (positive electrode active material having a ratio of average particle size to average primary particle size of 5 or less) in the positive electrode active material layer is preferably 50% to 99% by mass, more preferably 70% to 98% by mass, and further preferably 80% to 95% by mass. By making the content of the single-particle system particles in the positive electrode active material layer within the above range, the capacity retention rate after charge and discharge cycles can be further improved.

[0061] The positive electrode active material layer may contain other positive electrode active materials other than single particle particles (positive electrode active materials having a ratio of average particle size to average primary particle size of 5 or less). Single particle particles and other positive electrode active materials (positive electrode active materials having a ratio of average particle size to average primary particle size of more than 5) may be positive electrode active materials composed of different materials. However, the content of single particle particles in all positive electrode active materials contained in the positive electrode active material layer is preferably 80% by mass to 100% by mass, more preferably 95% by mass to 100% by mass, and further preferably 100% by mass. In other words, the ratio of the average particle size of all positive electrode active materials contained in the positive electrode active material layer to the average primary particle size is preferably 5 or less, more preferably 4 or less, 3 or less or 2.5 or less. In this case, the capacity retention rate after charge and discharge cycles can be further improved. The ratio of the average particle size of all positive electrode active materials contained in the positive electrode active material layer to the average primary particle size can be 0.9 or more, or 1 or more. The ratio of the average particle size based on all the positive electrode active material particles contained in the positive electrode active material layer to the average primary particle size may be greater than any of the lower limits described above and greater than any of the upper limits described above.

[0062] The content of all positive electrode active materials in the positive electrode active material layer is preferably 50% to 99% by mass, more preferably 70% to 98% by mass, and further preferably 80% to 95% by mass. By making the content of the positive electrode active material within the above range, both high energy density and manufacturability of the positive electrode active material layer can be achieved.

[0063] The conductive agent is not particularly limited as long as it is a material with conductivity. As such a conductive agent, for example, carbonaceous materials, metals, conductive ceramics, etc. can be mentioned. As carbonaceous materials, graphite, non-graphite carbon, graphene-based carbon, etc. can be mentioned. As non-graphite carbon, carbon nanofibers, pitch-based carbon fibers, carbon black, etc. can be mentioned. As carbon black, furnace black, acetylene black, Ketjen black, etc. can be mentioned. As graphene-based carbon, graphene, carbon nanotubes (CNT), fullerene, etc. can be mentioned. As the shape of the conductive agent, powder, fiber, etc. can be mentioned. As the conductive agent, one of these materials can be used alone, or two or more can be mixed and used. In addition, these materials can also be used in a composite. For example, a material obtained by composite carbon black and CNT can be used. Among them, from the viewpoint of electronic conductivity and coating properties, carbon black is preferred, and acetylene black is preferred.

[0064] The content of the conductive agent in the positive electrode active material layer is preferably 1% to 10% by mass, more preferably 3% to 9% by mass. When the content of the conductive agent is within the above range, the energy density of the nonaqueous electrolyte storage device can be increased.

[0065] Examples of adhesives include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic acid, and polyimide; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), and fluororubber; and polysaccharide polymers.

[0066] The content of the binder in the positive electrode active material layer is preferably 1% by mass to 10% by mass, and more preferably 3% by mass to 9% by mass. When the content of the binder is within the above range, the positive electrode active material can be stably retained.

[0067] As thickeners, for example, polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose can be cited. In the case where the thickener has a functional group that reacts with lithium or the like, the functional group can be deactivated in advance by methylation or the like. In the case where a thickener is used in the positive electrode active material layer, the content of the thickener in the positive electrode active material layer can be set to 0.1% by mass to 8% by mass, usually preferably less than 5% by mass, more preferably less than 2% by mass. The technology disclosed herein can preferably be implemented in a manner where the positive electrode active material layer does not contain a thickener.

[0068] The filler is not particularly limited. As fillers, polyolefins such as polypropylene and polyethylene can be cited; inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide; carbonates such as calcium carbonate; insoluble ionic crystals such as calcium fluoride, barium fluoride, and barium sulfate; nitrides such as aluminum nitride and silicon nitride; talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, mica, etc. from mineral resources or their artificial products. In the case of using a filler in the positive electrode active material layer, the content of the filler in the positive electrode active material layer can be set to 0.1% by mass to 8% by mass, preferably 5% by mass or less, and more preferably 2% by mass or less. The technology disclosed herein can preferably be implemented in a manner where the positive electrode active material layer does not contain a filler.

[0069] The positive electrode active material layer may contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.

[0070] (negative electrode)

[0071] The negative electrode comprises a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The structure of the intermediate layer is not particularly limited, and can be selected from the structures exemplified for the positive electrode described above.

[0072] The negative electrode substrate has conductivity. As the material of the negative electrode substrate, metals such as copper, nickel, stainless steel, nickel-plated steel, aluminum, or their alloys, carbonaceous materials, etc. can be used. Among them, copper or copper alloys are preferred. As the negative electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the perspective of cost, foil is preferred. Therefore, as the negative electrode substrate, copper foil or copper alloy foil is preferred. As examples of copper foil, rolled copper foil, electrolytic copper foil, etc. can be cited.

[0073] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By making the average thickness of the negative electrode substrate within the above range, the strength of the negative electrode substrate can be increased, and the energy density per unit volume of the non-aqueous electrolyte storage element can be increased.

[0074] The negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer contains any component such as a conductive agent, a binder, a thickener, and a filler as needed. The conductive agent, the binder, the thickener, the filler, and any component can be selected from the materials exemplified for the positive electrode.

[0075] The negative electrode active material layer may contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, W as ingredients other than the negative electrode active material, conductive agent, binder, thickener and filler.

[0076] As the negative electrode active material, it can be appropriately selected from known negative electrode active materials. As the negative electrode active material for lithium ion secondary batteries, materials that can absorb and release lithium ions are generally used. Examples of the negative electrode active material include metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li4Ti5O 12 , LiTiO2, TiNb2O7 and other titanium-containing oxides; polyphosphate compounds; silicon carbide; carbon materials such as graphite and non-graphite carbon (easy graphitization carbon or difficult graphitization carbon). Among these materials, graphite and non-graphite carbon are preferred, and graphite is more preferred. In the negative electrode active material layer, one of these materials can be used alone, or two or more can be mixed and used.

[0077] “Graphite” refers to the average lattice spacing (d) of the (002) plane determined by X-ray diffraction before charge / discharge or in a discharged state. 002 ) is a carbon material having a diameter of 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. From the perspective of obtaining a material with stable physical properties, artificial graphite is preferred.

[0078] “Non-graphite carbon” refers to the average lattice spacing (d ) of the (002) plane determined by X-ray diffraction before charge / discharge or in a discharged state. 002 ) is a carbon material having a carbon thickness of 0.34 nm to 0.42 nm. Examples of non-graphite carbon include difficult-graphitization carbon and easy-graphitization carbon. Examples of non-graphite carbon include materials derived from resins, petroleum asphalt or materials derived from petroleum asphalt, petroleum coke or materials derived from petroleum coke, materials derived from plants, materials derived from alcohols, and the like.

[0079] Here, the "discharge state" refers to a state in which lithium ions that can be absorbed and released during charge and discharge can be fully released from the carbon material as the negative electrode active material. For example, the following state: in a half-cell using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metal Li as a counter electrode, the open circuit voltage is 0.7V or more.

[0080] "Difficult to graphitize carbon" refers to the above-mentioned 002 It is a carbon material with a diameter of 0.36nm to 0.42nm.

[0081] "Easily graphitizable carbon" refers to the above-mentioned 002 A carbon material having a diameter of 0.34 nm or more and less than 0.36 nm.

[0082] The negative electrode active material is usually a particle (powder). The average particle size of the negative electrode active material can be set to 1nm to 100μm, for example. When the negative electrode active material is a carbon material, a titanium-containing oxide or a polyphosphate compound, its average particle size can be 1μm to 100μm. When the negative electrode active material is Si, Sn, Si oxide or Sn oxide, etc., its average particle size can be 1nm to 1μm. By making the average particle size of the negative electrode active material above the above lower limit, the manufacture or handling of the negative electrode active material becomes easy. By making the average particle size of the negative electrode active material below the above upper limit, the electronic conductivity of the negative electrode active material layer is improved. In order to obtain a powder with a specified particle size, a pulverizer, a classifier, etc. can be used. The pulverization method and the classification method can be selected from the methods exemplified for the above-mentioned positive electrode, for example. When the negative electrode active material is a metal such as metal Li, the negative electrode active material layer can be in the form of a foil.

[0083] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% to 99% by mass, more preferably 90% to 98% by mass. When the content of the negative electrode active material is within the above range, both high energy density and manufacturability of the negative electrode active material layer can be achieved.

[0084] When a conductive agent is used in the negative electrode active material layer, the content of the conductive agent in the negative electrode active material layer may be 1% to 10% by mass, or 3% to 9% by mass. When the negative electrode active material is a carbon material, the negative electrode active material layer may not contain a conductive agent.

[0085] The content of the binder in the negative electrode active material layer is preferably 1% by mass to 10% by mass, and more preferably 3% by mass to 9% by mass. When the content of the binder is within the above range, the negative electrode active material can be stably retained.

[0086] The content of the thickener in the negative electrode active material layer is preferably 0.1% by mass to 8% by mass, and more preferably 0.3% by mass to 5% by mass.

[0087] When a filler is used in the negative electrode active material layer, the content of the filler in the negative electrode active material layer can be set to 0.1 mass % to 8 mass %, usually preferably 5 mass % or less, more preferably 2 mass % or less. The technology disclosed herein can be preferably implemented in a manner that the negative electrode active material layer does not contain a filler.

[0088] (Isolator)

[0089] The separator can be appropriately selected from known separators. As the separator, for example, a separator consisting only of a substrate layer, a separator having a heat-resistant layer containing heat-resistant particles and an adhesive formed on one or both surfaces of the substrate layer, etc. can be used. As the shape of the substrate layer of the separator, for example, woven fabrics, non-woven fabrics, porous resin films, etc. can be cited. Among these shapes, porous resin films are preferred from the viewpoint of strength, and non-woven fabrics are preferred from the viewpoint of liquid retention of non-aqueous electrolytes. As the material of the substrate layer of the separator, from the viewpoint of the shutdown function, for example, polyolefins such as polyethylene and polypropylene are preferred, and from the viewpoint of resistance to oxidative decomposition, for example, polyimides, aromatic polyamides, etc. are preferred. As the substrate layer of the separator, a material composited with these resins can be used.

[0090] The heat-resistant particles contained in the heat-resistant layer preferably have a mass reduction of 5% or less when the temperature is increased from room temperature to 500°C in an air atmosphere of 1 atmosphere, and more preferably have a mass reduction of 5% or less when the temperature is increased from room temperature to 800°C. As materials whose mass reduction is less than the prescribed value, inorganic compounds can be cited. As inorganic compounds, for example, oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminum silicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; insoluble ionic crystals such as calcium fluoride, barium fluoride, and barium titanate; covalently bonded crystals such as silicon and diamond; talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, mica, etc., or their artificial products, etc. As inorganic compounds, monomers or complexes of these substances can be used alone, or two or more can be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of safety of the nonaqueous electrolyte storage element.

[0091] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, the "porosity" is a value based on volume, and refers to a value measured by a mercury porosimeter.

[0092] As a separator, a polymer gel composed of a polymer and a non-aqueous electrolyte can be used. Examples of the polymer include polypropylene, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyvinylidene fluoride, and the like. When a polymer gel is used, leakage is suppressed. As a separator, a porous resin film or a nonwoven fabric as described above can be used together with the polymer gel.

[0093] (Non-aqueous electrolyte)

[0094] The non-aqueous electrolyte contains a compound containing sulfur (hereinafter also referred to as a "sulfur compound"). The sulfur compound is generally an organic compound containing sulfur. In one embodiment of the present invention, the sulfur compound may be a non-ionic compound. Examples of the sulfur compound include sulfates, sulfonates, sulfones, sulfites, sulfoxides, sulfides, disulfides, and the like. One or more sulfur compounds may be used.

[0095] Sulfate esters refer to compounds containing a structure in which two carbon atoms are respectively bonded to an oxysulfonyloxy group (-O-S(=O)2-O-). Examples of sulfate esters include cyclic sulfate esters and chain sulfate esters. Specific examples of cyclic sulfate esters include vinyl sulfate, 1,3-propylene sulfate, 2,3-propylene sulfate, 4,5-pentenyl sulfate, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, etc. Specific examples of chain sulfate esters include dimethyl sulfate, diethyl sulfate, etc.

[0096] Sulfonic acid esters refer to compounds having a structure in which two carbon atoms are bonded to a sulfonyloxy group (-S(=O)2O-). Examples of sulfonic acid esters include cyclic sulfonic acid esters and chain sulfonic acid esters. Specific examples of cyclic sulfonic acid esters include 1,3-propane sultone, 1,4-butane sultone, 1,3-propene sultone, 1,4-butene sultone, 1-methyl-1,3-propene sultone, 2-methyl-1,3-propene sultone, and 3-methyl-1,3-propene sultone. Specific examples of chain sulfonic acid esters include methyl methanesulfonate and ethyl methanesulfonate.

[0097] Sulfones refer to compounds containing a structure in which two carbon atoms are respectively bonded to a sulfonyl group (-S(=O)2-). Examples of sulfones include cyclic sulfones and chain sulfones. Specific examples of cyclic sulfones include sulfolane, 3-methylsulfolane, 3-sulfolene, 1,1-dioxythiophene, 3-methyl-2,5-dihydrothiophene-1,1-dioxide, and 3-sulfolene-3-carboxylic acid methyl ester. Specific examples of chain sulfones include dimethyl sulfone, diethyl sulfone, ethyl methyl sulfone, and divinyl sulfone.

[0098] Sulfites refer to compounds having a structure in which two carbon atoms are bonded to an oxysulfinyloxy group (-O-S(=O)-O-). Examples of sulfites include cyclic sulfites and chain sulfites. Specific examples of cyclic sulfites include vinyl sulfite, 1,2-propylene glycol sulfite, trimethylene sulfite, 1,3-butylene glycol sulfite, etc. Specific examples of chain sulfites include dimethyl sulfite, diethyl sulfite, etc.

[0099] Sulfoxides refer to compounds having a structure in which two carbon atoms are respectively bonded to a sulfinyl group (-S(=O)-). Examples of sulfoxides include cyclic sulfoxides and chain sulfoxides. Specific examples of cyclic sulfoxides include tetramethylene sulfoxide. Specific examples of chain sulfoxides include dimethyl sulfoxide and diethyl sulfoxide.

[0100] Sulfides refer to compounds containing a structure in which two carbon atoms are respectively bonded to divalent sulfur (-S-). Examples of sulfides include cyclic sulfides and chain sulfides. Specific examples of cyclic sulfides include tetrahydrothiophene, thiophene, cyclopentane sulfide, 1,3-dithiane, 5,6-dihydro-1,4-dithiene-2,3-dicarboxylic anhydride, and 3,4-thiophene dicarboxylic anhydride. Specific examples of chain sulfides include diallyl sulfide, diphenyl sulfide, and thioanisole.

[0101] Disulfides refer to compounds having a structure in which two carbon atoms are bonded to a disulfide group (-S-S-). Examples of disulfides include cyclic disulfides and chain disulfides. Specific examples of disulfides include diphenyl disulfide, bipyridine disulfide, Disulfide, diallyl disulfide, etc.

[0102] As the sulfur compound, a compound containing a sulfonyl (-S(=O)2-) structure is preferred. As such a compound, the above-mentioned sulfates, sulfonates, sulfones, etc. can be cited, and sulfates are preferred. By using sulfates as the sulfur compound, in addition to the high capacity retention rate after charge and discharge cycles, the initial DC resistance of the non-aqueous electrolyte storage element can also be reduced.

[0103] Among the sulfates, preferred are vinyl sulfate, 1,3-propylene sulfate, 2,3-propylene sulfate, 4,5-pentenyl sulfate, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane) and 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane. The sulfur atom content per unit molecular weight or the sulfonyl structure content per unit molecular weight of these compounds is the same. Therefore, in particular, when any of these compounds is used, if the content (mass %) in the nonaqueous electrolyte is the same, the same effect can be expected. In addition, the sulfates preferably have multiple oxysulfonyloxy groups in one molecule, and also preferably have multiple ring structures and each ring structure has an oxysulfonyloxy group.

[0104] As the sulfur-based compound, a compound having a ring structure is preferred, a compound containing sulfur in the ring structure is more preferred, a compound containing a sulfonyl group in the ring structure is further preferred, and a compound containing an oxysulfonyloxy group in the ring structure is particularly preferred. The sulfur-based compound preferably contains sulfur and oxygen elements, and is more preferably composed of sulfur, oxygen, carbon and hydrogen. The sulfur-based compound preferably has two sulfonyl groups or two oxysulfonyloxy groups in one molecule. In addition, the sulfur-based compound is preferably a molecular compound of a nonionic compound. Such a compound can further improve the capacity retention rate after the charge and discharge cycle by effectively producing decomposition during the initial charge and discharge.

[0105] As the content of the sulfur compound in the non-aqueous electrolyte, it is preferably more than 0% by mass and less than 5% by mass, more preferably 0.01% by mass to 3% by mass, further preferably 0.05% by mass to 2% by mass, further preferably 0.1% by mass to 1.5% by mass, further preferably 0.2% by mass to 1.0% by mass, and further preferably 0.3% by mass to 0.8% by mass. The upper limit of this content may be 0.6% by mass or 0.4% by mass. By making the content of the sulfur compound within the above range, the capacity retention rate after the charge and discharge cycle can be further improved, and the DC resistance after the charge and discharge cycle can be reduced. It should be noted that at least a part of the sulfur compound contained in the non-aqueous electrolyte is decomposed during the initial charge and discharge to form a film covering the active material of the positive electrode and the negative electrode. Therefore, if it can be confirmed that a small amount of sulfur compound remains in the non-aqueous electrolyte possessed by the non-aqueous electrolyte storage element, it can be said that a sufficient film has been formed on the surface of the active material of the positive electrode and the negative electrode, so the effect of suppressing the reduction of the discharge capacity brought by the sulfur compound can be achieved.

[0106] The non-aqueous electrolyte may be a non-aqueous electrolyte solution containing a non-aqueous solvent, an electrolyte salt dissolved in the non-aqueous solvent, and the above-mentioned sulfur-based compound.

[0107] As nonaqueous solvent, it is possible to suitably select from known nonaqueous solvents. As nonaqueous solvent, cyclic carbonate, linear carbonate, carboxylate, phosphoric acid ester, ether, amides, nitrile etc. can be enumerated. As nonaqueous solvent, it is also possible to use a nonaqueous solvent in which a part of the hydrogen atom included in these compounds is replaced by halogen.

[0108] Examples of the cyclic carbonate include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Among them, EC and PC are preferred.

[0109] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, ethyl methyl trifluorocarbonate, bis(trifluoroethyl) carbonate, etc. Among them, EMC is preferred.

[0110] As non-aqueous solvent, preferably use cyclic carbonate or chain carbonate, more preferably use cyclic carbonate and chain carbonate.By using cyclic carbonate, can promote the dissociation of electrolyte salt, improve the ion conductivity of non-aqueous electrolyte.By using chain carbonate, can suppress the viscosity of non-aqueous electrolyte to be low.When using cyclic carbonate and chain carbonate, as the volume ratio of cyclic carbonate and chain carbonate (cyclic carbonate: chain carbonate), for example, preferably set to the range of from 5:95 to 50:50.

[0111] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, Among them, lithium salts are preferred.

[0112] As lithium salts, inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, lithium oxalate salts such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalate borate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP) can be cited. Among them, inorganic lithium salts are preferred, and LiPF6 is more preferred. In addition, as a lithium salt, lithium difluorophosphate (LiPO2F2) is also preferably used. As a lithium salt, it is more preferred to use LiPF6 and LiPO2F2 in combination.

[0113] The content of the electrolyte salt in the non-aqueous electrolyte is preferably 0.1 mol / dm 3 ~2.5mol / dm 3 , more preferably 0.3 mol / dm 3 ~2.0mol / dm3 , more preferably 0.5 mol / dm 3 ~1.7mol / dm 3 , particularly preferably 0.7 mol / dm 3 ~1.5mol / dm 3 By setting the content of the electrolyte salt to be within the above range, the ion conductivity of the non-aqueous electrolyte can be improved.

[0114] When LiPO 2 F 2 is used, the content of LiPO 2 F 2 in the non-aqueous electrolyte may be, for example, 0.01% by mass to 2% by mass, or 0.1% by mass to 1% by mass.

[0115] The nonaqueous electrolyte solution may contain other components in addition to the sulfur-based compound, the nonaqueous solvent, and the electrolyte salt. As other components, for example, there can be mentioned aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partial hydrogenation of terphenyl, cyclohexylbenzene, tert-butylbenzene, tert-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, and cyclohexanedicarboxylic anhydride; perfluorooctane, tris(trimethylsilyl)borate, tris(trimethylsilyl)phosphate, tetrakis(trimethylsilyl)titanate, and lithium monofluorophosphate. These other components may be used alone or in combination of two or more.

[0116] The content of the above-mentioned other components contained in the non-aqueous electrolyte is preferably 0.01% to 10% by mass, more preferably 0.1% to 7% by mass, further preferably 0.2% to 5% by mass, and particularly preferably 0.3% to 3% by mass relative to the mass of the entire non-aqueous electrolyte. By making the content of the above-mentioned other components within the above range, the capacity retention performance or cycle performance after high temperature storage can be improved, or the safety can be further improved.

[0117] As a non-aqueous electrolyte, a non-aqueous electrolyte and a solid electrolyte can be used in combination. As a solid electrolyte, it can be selected from any material that has ion conductivity and is solid at room temperature (e.g., 15° C. to 25° C.), such as lithium, sodium, and calcium. As a solid electrolyte, for example, a sulfide solid electrolyte, an oxide solid electrolyte, a nitride solid electrolyte, a polymer solid electrolyte, and the like can be cited.

[0118] (Positive electrode potential at discharge end voltage during normal use)

[0119] The upper limit of the positive electrode potential of the discharge end voltage of the nonaqueous electrolyte storage element of one embodiment of the present invention during normal use is 3.5 V (vs. Li / Li + ), preferably 3.2V (vs. Li / Li + ), more preferably 3.0V (vs.Li / Li + By making the positive electrode potential of the discharge end voltage during normal use below the above upper limit, the discharge capacity of the non-aqueous electrolyte storage element can be increased. As the lower limit of the positive electrode potential, it is preferably 2.6V (vs. Li / Li + ), more preferably 2.7V (vs. Li / Li + ), more preferably 2.8V (vs. Li / Li + ), and more preferably 2.9V (vs. Li / Li + ). By making the positive electrode potential of the discharge end voltage during normal use above the lower limit, the capacity retention rate after the charge and discharge cycle can be further improved. The positive electrode potential can be set to any of the lower limits to any of the upper limits.

[0120] The shape of the nonaqueous electrolyte storage element of the present embodiment is not particularly limited, and examples thereof include cylindrical batteries, square batteries, flat batteries, coin batteries, and button batteries.

[0121] Figure 1 A non-aqueous electrolyte storage element 1 is shown as an example of a square battery. It should be noted that this figure is a perspective view of the inside of a container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a square container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.

[0122] <Electricity storage device>

[0123] The non-aqueous electrolyte storage element of the present embodiment can be mounted as a storage unit (battery module) composed of a plurality of non-aqueous electrolyte storage elements in an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV) and other automotive power sources, a power source for electronic devices such as a personal computer and a communication terminal, or a power source for power storage, etc. In this case, the technology of the present invention can be applied to at least one non-aqueous electrolyte storage element included in the storage unit.

[0124] Figure 2An example of an electric storage device 30 is shown in which an electric storage unit 20 composed of two or more electrically connected non-aqueous electrolyte storage elements 1 is further assembled. The electric storage device 30 may include a bus bar (not shown) electrically connecting the two or more non-aqueous electrolyte storage elements 1, a bus bar (not shown) electrically connecting the two or more electric storage units 20, etc. The electric storage unit 20 or the electric storage device 30 may also include a state monitoring device (not shown) for monitoring the state of one or more non-aqueous electrolyte storage elements 1.

[0125] <Equipment>

[0126] A device according to one embodiment of the present invention includes the nonaqueous electrolyte storage element according to one embodiment of the present invention. The device may be, without particular limitation, electronic devices such as personal computers and communication terminals, home appliances, automobiles (EV, HEV, PHEV, etc.), or other industrial equipment.

[0127] The device is preferably used in normal use with a positive electrode potential of 3.5 V (vs. Li / Li) at the discharge end voltage of the non-aqueous electrolyte storage element. + ) is set as follows. By setting in this way, the discharge capacity of the non-aqueous electrolyte storage element of the device becomes larger. In addition, the non-aqueous electrolyte storage element of the device has a positive electrode potential of 3.5V (vs. Li / Li + ) is used to set the discharge cut-off voltage in the following manner, and the capacity retention rate after the charge-discharge cycle is also high. The preferred range of the positive electrode potential of the discharge cut-off voltage of the non-aqueous electrolyte storage element set in the device is the same as the above-mentioned preferred range of the positive electrode potential of the discharge cut-off voltage when the non-aqueous electrolyte storage element is normally used. The device preferably has a control device for controlling the discharge cut-off voltage, etc.

[0128] <How to use non-aqueous electrolyte storage devices>

[0129] A method for using a non-aqueous electrolyte storage element according to an embodiment of the present invention comprises: discharging a non-aqueous electrolyte storage element having a positive electrode including a positive electrode active material having a ratio of an average particle size to an average primary particle size of 5 or less and a non-aqueous electrolyte including a compound containing a sulfur element until the positive electrode potential reaches 3.5 V (vs. Li / Li + )the following.

[0130] In this method of use, the non-aqueous electrolyte storage element of one embodiment of the present invention described above can be preferably used. In addition, the preferred range of the lower limit potential of the positive electrode (the lower limit value of the positive electrode potential) during discharge in this method of use is the same as the above-mentioned range of the preferred range of the positive electrode potential of the discharge termination voltage when the non-aqueous electrolyte storage element is normally used. In this method of use, the device of one embodiment of the present invention described above can be preferably used. In this method of use, even if the positive electrode potential of the non-aqueous electrolyte storage element reaches 3.5V (vs. Li / Li) during discharge + ) or less, but the capacity retention rate after charge and discharge cycles is high.

[0131] <Method for producing non-aqueous electrolyte storage element>

[0132] A method for producing a nonaqueous electrolyte storage element according to an embodiment of the present invention is to have a positive electrode potential of 3.5 V (vs. Li / Li) at a discharge end voltage during normal use. + ) or less, comprising: preparing a positive electrode containing a positive electrode active material having a ratio of an average particle size to an average primary particle size of 5 or less; and preparing a nonaqueous electrolyte containing a compound containing elemental sulfur. The content of the compound containing elemental sulfur in the prepared nonaqueous electrolyte is preferably 0.5 mass % or more.

[0133] Preparing the positive electrode may be making the positive electrode. The making of the positive electrode may be carried out, for example, by applying a positive electrode mixture paste directly or via an intermediate layer to the positive electrode substrate and drying it. After drying, pressing may be performed as needed. The positive electrode mixture paste contains a positive electrode active material and various components constituting a positive electrode active material layer such as a conductive agent and a binder as arbitrary components. The positive electrode mixture paste generally further contains a dispersion medium. The specific form and preferred form of the prepared positive electrode are the same as the specific form and preferred form of the positive electrode possessed by the non-aqueous electrolyte storage element of one embodiment of the present invention described above.

[0134] Preparing a non-aqueous electrolyte may be preparing a non-aqueous electrolyte. The preparation of a non-aqueous electrolyte may be carried out, for example, by mixing a non-aqueous solvent, an electrolyte salt and a sulfur compound. The content of the sulfur compound in the prepared non-aqueous electrolyte is preferably 0.01% by mass to 5% by mass, more preferably 0.1% by mass to 3% by mass, further preferably 0.2% by mass to 2% by mass, and further preferably 0.3% by mass to 1.5% by mass. The lower limit of the content may be 0.5% by mass, 0.7% by mass, 0.9% by mass or 1.1% by mass. In addition, the specific form and preferred form of the prepared non-aqueous electrolyte are the same as the specific form and preferred form of the non-aqueous electrolyte possessed by the non-aqueous electrolyte storage element of one embodiment of the present invention described above.

[0135] The manufacturing method may further include: preparing a negative electrode, preparing a separator, stacking or winding the separator via the positive electrode and the negative electrode to form an electrode body, storing the electrode body and the non-aqueous electrolyte in a container, and performing initial charge and discharge. Usually, by performing the initial charge and discharge, at least a portion of the sulfur compound is decomposed to form a film of the active material covering the positive electrode and the negative electrode. The specific form and preferred form of the prepared negative electrode and separator are the same as the specific form and preferred form of the negative electrode and separator of the non-aqueous electrolyte storage element of one embodiment of the present invention.

[0136] The nonaqueous electrolyte may be stored in the container by any known method. For example, when a nonaqueous electrolyte solution is used as the nonaqueous electrolyte, the nonaqueous electrolyte solution may be injected from an injection port formed in the container and then the injection port may be sealed.

[0137] <Other embodiments>

[0138] It should be noted that the nonaqueous electrolyte storage element, device, method for using the nonaqueous electrolyte storage element and method for manufacturing the nonaqueous electrolyte storage element of the present invention are not limited to the above-mentioned embodiments, and various changes can be added without departing from the scope of the present invention. For example, the structure of other embodiments can be added to the structure of a certain embodiment, and in addition, a part of the structure of a certain embodiment can be replaced with the structure of other embodiments or known technology. Furthermore, a part of the structure of a certain embodiment can be deleted. In addition, known technology can be added to the structure of a certain embodiment.

[0139] In the above embodiment, the case where the nonaqueous electrolyte storage element is used as a nonaqueous electrolyte secondary battery (e.g., a lithium ion secondary battery) capable of charge and discharge is described, but the type, shape, size, capacity, etc. of the nonaqueous electrolyte storage element are arbitrary. The present invention can also be applied to capacitors such as various secondary batteries, double-layer capacitors, or lithium ion capacitors.

[0140] In the above embodiment, the electrode body is described as a stacked positive electrode and a negative electrode with a separator interposed therebetween, but the electrode body may not include a separator. For example, the positive electrode and the negative electrode may be in direct contact with each other with a non-conductive layer formed on the active material layer of the positive electrode or the negative electrode.

[0141] Example

[0142] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to the following examples.

[0143] [Example 1]

[0144] (Production of positive electrode)

[0145] As a positive electrode active material, Li having an average primary particle size of 2.5 μm, an average particle size of 5.5 μm, and a ratio of the average particle size to the average primary particle size of 2.2 was prepared. 1.0 Ni 0.6 Co 0.2 Mn 0.2 O2 (single particle system particles).

[0146] A positive electrode mixture paste containing the above-mentioned positive electrode active material (single particle system particles), polyvinylidene fluoride (PVDF) as a binder, and acetylene black (AB) as a conductive agent, and N-methylpyrrolidone (NMP) as a dispersion medium is prepared. The mass ratio of the positive electrode active material, the binder, and the conductive agent is set to 94.5:1.5:4.0 in terms of solid content conversion. The positive electrode mixture paste is applied to an aluminum foil as a positive electrode substrate, dried, and pressed to form a positive electrode active material layer. Thus, a positive electrode having a positive electrode active material layer stacked on a positive electrode substrate is obtained.

[0147] (Production of negative electrode)

[0148] A negative electrode mixture paste containing graphite as a negative electrode active material, styrene butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener and water as a dispersion medium is prepared. The mass ratio of the negative electrode active material, the binder, and the thickener is set to 97.8:1.0:1.2 in terms of solid content conversion. The negative electrode mixture paste is applied to a copper foil as a negative electrode substrate and dried, and pressed to form a negative electrode active material layer. Thus, a negative electrode having a negative electrode active material layer stacked on a negative electrode substrate is obtained.

[0149] (Preparation of non-aqueous electrolyte)

[0150] In a non-aqueous solvent prepared by mixing ethylene carbonate (EC), propylene carbonate (PC) and ethyl methyl carbonate (EMC) in a volume ratio of 25:5:70, 1.0 mol / dm 3 Lithium hexafluorophosphate (LiPF6) was mixed at a concentration of 0.75 mass % of sulfur compound A (4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane)) and lithium difluorophosphate (LiPO2F2) were mixed at a content of 0.50 mass % in the mixed solution to prepare a non-aqueous electrolyte.

[0151] (Assembly of non-aqueous electrolyte storage element)

[0152] The positive electrode and the negative electrode were stacked with a polyethylene microporous film separator interposed therebetween to produce an electrode body. The electrode body was housed in a container, and the nonaqueous electrolyte was injected into the container to obtain the nonaqueous electrolyte storage element of Example 1.

[0153] [Examples 2 to 3]

[0154] Except that the content of the sulfur-based compound A contained in the non-aqueous electrolyte was set as described in Table 1, the same procedure as in Example 1 was carried out to obtain non-aqueous electrolyte storage devices of Examples 2 and 3.

[0155] [Comparative Example 1, Reference Example 1]

[0156] (Production of positive electrode)

[0157] As a positive electrode active material, Li having an average primary particle size of 0.6 μm, an average particle size of 8.5 μm, and a ratio of the average particle size to the average primary particle size of 14.2 was prepared. 1.0 Ni 0.6 Co 0.2 Mn 0.2 O2 (Secondary Particles) A ​​positive electrode was obtained in the same manner as in Example 1 except that the above-mentioned secondary particles were used as the positive electrode active material.

[0158] (Production of negative electrode)

[0159] In the same manner as in Example 1, a negative electrode was obtained.

[0160] (Preparation of non-aqueous electrolyte)

[0161] In a non-aqueous solvent prepared by mixing ethylene carbonate (EC), propylene carbonate (PC) and ethyl methyl carbonate (EMC) in a volume ratio of 25:5:70, 1.0 mol / dm 3 Lithium hexafluorophosphate (LiPF6) was mixed at a concentration of 0.40 mass % of vinylene carbonate (VC) and lithium difluorophosphate (LiPO2F2) were mixed at a content of 0.50 mass % in the mixed solution to obtain a non-aqueous electrolyte.

[0162] (Assembly of non-aqueous electrolyte storage element)

[0163] The positive electrode and the negative electrode are stacked via a polyethylene microporous membrane separator to make an electrode body. The electrode body is housed in a container, and the non-aqueous electrolyte is injected into the container to obtain each non-aqueous electrolyte storage element of Comparative Example 1 and Reference Example 1. It should be noted that the non-aqueous electrolyte storage element of Comparative Example 1 is different from the non-aqueous electrolyte storage element of Reference Example 1 only in the charge and discharge conditions described later, and is the same as a structure. The same is true for the non-aqueous electrolyte storage element of Comparative Example 2 described later and the non-aqueous electrolyte storage element of Reference Example 2.

[0164] [Comparative Examples 2 to 4, Reference Examples 2 to 4]

[0165] Each nonaqueous electrolyte storage device of Comparative Examples 2 to 4 and Reference Examples 2 to 4 was obtained in the same manner as in Comparative Example 1 and Reference Example 1, except that the sulfur-based compound A was contained in the nonaqueous electrolyte in the amount described in Table 1.

[0166] [evaluate]

[0167] (Initial charge and discharge)

[0168] For each non-aqueous electrolyte storage element of the assembled Examples 1 to 3, Comparative Examples 1 to 4, and Reference Examples 1 to 4, the following initial charge and discharge were performed. At 25°C, constant current and constant voltage charging was performed under the conditions of a charging current of 1.0C and a charge end voltage of 4.25V until the charging time reached a total of 3 hours. Then, a 10-minute rest period was set. Next, constant current discharge was performed under the conditions of a discharge current of 1.0C and a discharge end voltage described in Table 1.

[0169] For each non-aqueous electrolyte storage element of Examples 1 to 3, the content of sulfur compound A (4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane)) in the non-aqueous electrolyte after the initial charge and discharge was measured by gas chromatography (GC). In Example 1, although the presence of sulfur compound A was confirmed by gas chromatography-mass spectrometry (GC-MS) measured separately, it was below the detection limit in GC, so the content of sulfur compound A could not be quantified. In Example 2, the content of sulfur compound A in the non-aqueous electrolyte after the initial charge and discharge was 0.25% by mass, and in Example 3, the content of sulfur compound A in the non-aqueous electrolyte after the initial charge and discharge was 0.36% by mass.

[0170] (Charge and discharge cycle test)

[0171] For each non-aqueous electrolyte storage element of Examples 1 to 3, Comparative Examples 1 to 4 and Reference Examples 1 to 4 that have undergone the above-mentioned initial charge and discharge, a charge and discharge cycle test was performed according to the following points. Constant current and constant voltage charging was performed at 45°C with a charging current of 1.0C and a charge termination voltage of 4.25V. The charge termination condition was set to the moment when the charging current decayed to 0.01C. Then, a constant current discharge was performed with a discharge current of 1.0C and a discharge termination voltage as described in Table 1. A rest period of 10 minutes was set after charging and after discharging, respectively. The charge and discharge was performed for 2000 cycles. It should be noted that Table 1 also represents the positive electrode potential of the discharge termination voltage.

[0172] (Capacity maintenance rate)

[0173] The percentage of the discharge capacity at the 2000th cycle relative to the discharge capacity at the 1st cycle of each of the nonaqueous electrolyte storage elements of Examples 1 to 3, Comparative Examples 1 to 4, and Reference Examples 1 to 4 was determined as the capacity retention rate.

[0174] (DC resistance)

[0175] For each non-aqueous electrolyte storage element of Examples 1 to 3, after 1000 cycles in the above-mentioned charge and discharge cycle test, the DC resistance is measured according to the following points. In a thermostatic chamber at 25°C, constant current charging with a charging current of 1.0C is performed to make the SOC 50%. Then, in a thermostatic chamber at -10°C, discharge for 30 seconds in the order of discharge currents of 0.2C, 0.5C, and 1.0C. After each discharge is completed, constant current charging is performed with a charging current of 0.05C to make the SOC 50%. The relationship between the discharge current at each discharge current and the voltage at the 10th second after the start of discharge is plotted, and the DC resistance (DCR) is calculated based on the slope of the straight line obtained from the three plotted points. For each DCR, it is shown in Table 1 as a relative value based on the value of Example 1 (100.0%).

[0176]

[0177] As shown in Reference Examples 1 to 4, when the positive electrode potential at the discharge end voltage is not 3.5 V (vs. Li / Li + ) or less, by including a sulfur compound in the non-aqueous electrolyte of a non-aqueous electrolyte storage element in which the positive electrode active material is a secondary particle, the capacity retention rate after charge and discharge cycles is improved. In addition, from the comparison between Comparative Example 1 and Reference Example 1, it can be seen that the positive electrode potential of the non-aqueous electrolyte storage element in which the positive electrode active material is a secondary particle is 3.5V (vs. Li / Li + ) or less, the capacity retention rate after the charge-discharge cycle is greatly reduced. Moreover, as shown in Comparative Examples 1 to 4, at the positive electrode potential of 3.5 V (vs. Li / Li + ) or less, even if the non-aqueous electrolyte of the non-aqueous electrolyte storage element in which the positive electrode active material is a secondary particle contains a sulfur-based compound, the capacity retention rate after the charge and discharge cycle does not improve but deteriorates. In contrast, as shown in Examples 1 to 3, when the positive electrode potential at the discharge end voltage is 3.5 V (vs. Li / Li + ) or less, by using single-particle particles as the positive electrode active material, it was confirmed that the sulfur-based compound contained in the non-aqueous electrolyte can suppress the decrease in the capacity retention rate after the charge-discharge cycle. In addition, the results of Examples 1 to 3 also confirmed the effect of reducing the DC resistance after the charge-discharge cycle by containing the sulfur-based compound.

[0178] [Reference Example 5]

[0179] (Production of positive electrode)

[0180] As a positive electrode active material, Li having an average primary particle size of 0.6 μm, an average particle size of 8.5 μm, and a ratio of the average particle size to the average primary particle size of 14.2 was prepared. 1.0 Ni 0.6 Co 0.2 Mn 0.2 O2 (secondary particles).

[0181] A positive electrode mixture paste containing the above-mentioned positive electrode active material (secondary particles), polyvinylidene fluoride (PVDF) as a binder, and acetylene black (AB) as a conductive agent, and N-methylpyrrolidone (NMP) as a dispersion medium is prepared. The mass ratio of the positive electrode active material, the binder, and the conductive agent is set to 94.5:1.5:4.0 in terms of solid content conversion. The positive electrode mixture paste is applied to an aluminum foil as a positive electrode substrate, dried, and pressed to form a positive electrode active material layer. Thus, a positive electrode having a positive electrode active material layer stacked on a positive electrode substrate is obtained.

[0182] (Production of negative electrode)

[0183] A negative electrode mixture paste containing graphite as a negative electrode active material, styrene butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener and water as a dispersion medium is prepared. The mass ratio of the negative electrode active material, the binder, and the thickener is set to 97.8:1.0:1.2 in terms of solid content conversion. The negative electrode mixture paste is applied to a copper foil as a negative electrode substrate and dried, and pressed to form a negative electrode active material layer. Thus, a negative electrode having a negative electrode active material layer stacked on a negative electrode substrate is obtained.

[0184] (Preparation of non-aqueous electrolyte)

[0185] In a non-aqueous solvent prepared by mixing ethylene carbonate (EC), propylene carbonate (PC) and ethyl methyl carbonate (EMC) in a volume ratio of 25:5:70, 1.0 mol / dm 3 Lithium hexafluorophosphate (LiPF6) was mixed at a concentration of 0.50 mass %. Sulfur compound A (4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane)) and vinylene carbonate (VC) were mixed at a content of 0.50 mass % in the mixed solution to prepare a non-aqueous electrolyte.

[0186] (Assembly of non-aqueous electrolyte storage element)

[0187] The positive electrode and the negative electrode were stacked with a polyethylene microporous film separator interposed therebetween to produce an electrode body. The electrode body was housed in a container, and the nonaqueous electrolyte was injected into the container to obtain a nonaqueous electrolyte storage element of Reference Example 5.

[0188] [Reference Example 6]

[0189] A nonaqueous electrolyte storage device of Reference Example 6 was obtained in the same manner as in Reference Example 5 except that the sulfur-based compound A contained in the nonaqueous electrolyte was replaced with the sulfur-based compound B (1,3-propene sultone).

[0190] [Comparative Example 5]

[0191] A nonaqueous electrolyte storage device of Comparative Example 5 was obtained in the same manner as in Reference Example 5 except that the sulfur-based compound A was not contained in the nonaqueous electrolyte.

[0192] [evaluate]

[0193] (Initial DC resistance)

[0194] For each non-aqueous electrolyte storage element of Reference Examples 5, 6 and Comparative Example 5, after the above-mentioned initial charge and discharge, the initial DC resistance is measured according to the following points. In a constant temperature chamber at 25°C, constant current charging with a charging current of 1.0C is performed to make the SOC 50%. Then, in a constant temperature chamber at -10°C, discharge for 30 seconds in the order of discharge currents of 0.2C, 0.5C, and 1.0C. After each discharge is completed, constant current charging is performed with a charging current of 0.05C to make the SOC 50%. The relationship between the discharge current at each discharge current and the voltage at the 10th second after the start of discharge is plotted, and the initial DC resistance (initial DCR) is calculated based on the slope of the straight line obtained from the three plotted points. For each initial DCR, it is shown in Table 2 as a relative value based on the value of Comparative Example 5 (100%).

[0195] [Table 2]

[0196]

[0197] A: 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane)

[0198] B: 1,3-Propene sultone

[0199] From the results of Reference Examples 5 and 6 and Comparative Example 5, it was confirmed that the initial direct current resistance of the nonaqueous electrolyte storage element can be reduced by using a sulfuric acid ester (sulfur compound A) as the sulfur compound.

[0200] Industrial Applicability

[0201] The present invention can be applied to non-aqueous electrolyte storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles.

[0202] Explanation of symbols

[0203] 1Non-aqueous electrolyte storage element

[0204] 2-electrode body

[0205] 3 Containers

[0206] 4 pole terminals

[0207] 41 positive lead

[0208] 5 Negative terminal

[0209] 51 negative lead

[0210] 20 Storage Unit

[0211] 30Electrical storage device

Claims

1. A non-aqueous electrolyte storage element, wherein the positive electrode potential of the discharge end voltage during normal use is 3.5 V (vs. Li / Li + ) and possess: A positive electrode containing a positive electrode active material having a ratio of average particle size to average primary particle size of 5 or less, and A non-aqueous electrolyte containing a compound containing elemental sulfur.

2. The nonaqueous electrolyte storage element according to claim 1, wherein The compound containing sulfur element is sulfate ester.

3. The nonaqueous electrolyte storage element according to claim 1 or 2, wherein: The nonaqueous electrolyte further contains lithium difluorophosphate. 4 . A device comprising the nonaqueous electrolyte storage element according to claim 1 .

5. A method for using a non-aqueous electrolyte storage element, comprising: discharging a non-aqueous electrolyte storage element having a positive electrode containing a positive electrode active material having a ratio of an average particle size to an average primary particle size of 5 or less and a non-aqueous electrolyte containing a compound containing a sulfur element until the positive electrode potential reaches 3.5 V (vs. Li / Li + )the following.

6. The positive electrode potential of a commonly used discharge termination voltage is 3.5V (vs. Li / Li + ) The method for manufacturing the following non-aqueous electrolyte storage element comprises: preparing a positive electrode containing a positive electrode active material having a ratio of an average particle size to an average primary particle size of 5 or less; and preparing a nonaqueous electrolyte containing a compound containing elemental sulfur; The content of the compound containing sulfur element in the non-aqueous electrolyte is 0.5 mass % or more.

Citation Information

Patent Citations

  • Nonaqueous secondary battery

    JP2003308875A